Controlled growth of bismuth antimony telluride BixSb2−xTe3 nanoplatelets and their bulk thermoelectric nanocomposites. (July 2015) - Zhang, Chaohua; Peng, Zeping; Li, Zhong; Yu, Ligen; Khor, Khiam Aik; Xiong, Qihua
Abstract: Solution synthesis as a scalable bottom-up growth method shows considerable advantages for designing novel nanostructured bulk composites with augmented thermoelectric performance. Tuning the composition of synthesized materials in the solution process is important for adjusting the carrier type and concentration. Here, we report a modified solvothermal synthesis method for the controlled growth of Bi x Sb2− x Te3 nanoplatelets, which can be sintered into nanostructured bulk pellets by using the spark plasma sintering process. We further demonstrate the tuning of the stoichiometric composition in ternary Bi x Sb2− x Te3 nanoplatelets with high crystallinity and homogenous phase purity, which is proved by X-ray diffraction and Raman spectroscopy. The composition dependence of the thermoelectric performance of p -type Bi x Sb2− x Te3 pellets is also systemically studied. The optimized nanostructured bulk Bi0.5 Sb1.5 Te3 sample is found to have ZT 0.51 at 375 K, which shows great potential for further improving the thermoelectric performance by this solution synthesis method. Considering the progress in n -type Bi–Te–Se composites, our results advocate the promise of bismuth/antimony chalcogenide nanocomposites towards practical thermoelectric applications. Graphical abstract: Highlights: Ternary p -type Bi x Sb2− x Te3 nanoplatelets are synthesized by a solvothermal method, using l -cysteine as reducing and stabilizing agent, which prevents phase segregation problem leading to homogenous composition. Bi x Sb2− x Te3 carrier concentration is systemically tuned. The crystalline phase and composition is investigated by X-ray diffraction and Raman spectroscopy. Bulk nanocomposites are formed by spark plasma sintering and the thermoelectric figure or merit of Bi x Sb2− x Te3 is optimized 0.51.